Higher functionality of extracellular vesicles isolated using size-exclusion chromatography compared to ultracentrifugation - Emma A. Mol; Marie‐José Goumans; Pieter A. Doevendans; Joost P. G. Sluijter; Pieter Vader (2017)
Extracellular vesicles (EVs) are nano-sized, lipid bilayer-enclosed particles involved in intercellular communication. EVs are increasingly being considered as drug delivery vehicles or as cell-free approach to regenerative medicine. However, one of the major challenges for their clinical application is finding a scalable EV isolation method that yields functional EVs. Although the golden standard for EV isolation is ultracentrifugation (UC), a recent study suggested that isolation using size-exclusion chromatography (SEC) yielded EVs with more intact biophysical properties. Whether this also leads to differences in functionality remained to be investigated. Therefore, we investigated possible differences in functionality of cardiomyocyte progenitor cell-derived EVs isolated using UC and SEC. Western blot analysis showed higher pERK/ERK ratios in endothelial cells after stimulation with SEC-EVs compared to UC-EVs, indicating that SEC-EVs bear higher functionality. Therefore, we propose to use SEC-EVs for further investigation of EVs' therapeutic potential. Further optimization of isolation protocols may accelerate clinical adoption of therapeutic EVs.